Roman Medan: Analisis Potret Sosial dalam Karya Sastra Masa Revolusi Indonesia di Sumatera Timur, 1945-1949 - Utari, Melly Tria (Local History & Heritage, 2023)
This article aims to elucidate the role of the literary work "Roman Medan" in depicting the socio-historical landscape of the Indonesian Revolution in East Sumatra. Employing a historical methodology and a social history approach, this research leverages various written sources, including "Roman Medan" stories published during the Indonesian Revolution era, newspapers, and supplementary literature. Despite the pervasive turmoil during the Revolution, authors and prominent figures did not remain silent; they endeavored to navigate through armed conflicts and diplomatic channels. In the context of East Sumatra, these efforts culminated in the creation of "Roman Medan." Unfortunately, these literary works have received limited attention, even though "Roman Medan" constitutes an authentic cultural product of the local community, offering profound insights into the lives of the people. The findings underscore that the conditions prevailing during the Revolution provided literary inspiration for authors. Through "Roman Medan" they conveyed the spirit of nationalism and offered a glimpse into the daily lives of individuals during this transformative period. Consequently, "Roman Medan" serves as a valuable resource for understanding the social realities of the Indonesian Revolution in East Sumatra.